Effects of rape and trauma on clothing behavior A multiple case study - Munez, Roshelle Sabrina L.
The effects of trauma on clothing behavior is not frequently discussed, especially in the Philippine context. Despite the lack of study, these clothing issues persist. This study aimed to describe and analyze clothing behavior changes due to rape and trauma in the Philippine context. To achieve this, seven female rape victims were interviewed in the study. Three clothing motivation theories were used to explain the clothing responses: Enclothed Cognition, Modesty Theory and Symbolic Interactionism. Results show that respondents had issues with clothing after an incident of rape. Respondents were found to cover up and wear loose and dark clothing. In addition, some were found to have changed into new positive styles, while others returned back to their old styles, and some did not change their styles at all. The study found that clothing response may be classified into two: (1) an initial reaction and (2) a secondary reaction. The former is observed 2-4 months after the incident, and the latter is 1-2 years after the incident. It was found that the initial reaction is affected by psychological impacts caused by the rape trauma, and the secondary reaction is a result of how the respondent has recovered from the trauma after a year or two. The respondents covered up as the initial reactions explained by the Modesty theory, and the secondary reactions can be explained by Symbolic Interactionism by how they reacted to the clothing based on its meaning. The respondents agreed that clothing can aid in coping, but believed that it may only be effective up to a certain extent only. Some respondents agreed that changing lingerie might be a coping mechanism that could empower the self. From the data gathered, it has been proven that clothing can show subconscious changes that the victim is not willing or able to verbalize.